Production and Characterization of Bamboo Fibre Reinforced PVC Composites - Fatin Nadiah, Abd Hamid (2012)
Since many years, efforts have been made to find ways to make natural fibre compatible enough with its matrix. The interest of using natural fibre reinforced polymer composites is growing rapidly due to their low cost and high performance in term of mechanical properties and thermal stability. In this study, the potential of alkali treatment with NaOH and maleic anhydride grafted PP (MAPP) as coupling agent adding on bamboo fibre particles as reinforcements for polyvinyl chloride (PVC) was investigated with the samples prepared by extrusion and compression molding. Two types of bamboo fibre were used which are untreated and treated with 5wt% NaOH concentration with both composition varying from10 to 30 wt%. Tensile properties showed that Young’s modulus increased with the increasing of fibre loading for all type of modifier, but have a little difference when 5% MAPP was added. Most of the results showed that the increasing bamboo fibre loading up to 20wt% increased the tensile strength but decreased back when 30wt% fibre loading were used. Using only 2.5% of MAPP with only 10wt% fibre loading have the highest tensile strength where the 30wt% fibre loading at the same amount of MAPP have the highest value of Young’s modulus. The adding of both modifiers also increased the thermal stability of this composite. The results of this study demonstrate that this composite had properties comparable with other conventional composite. Hence, the alkali treatment and MAPP was a competitive agent of creating bamboo fibre reinforced PVC composites.